The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2147/dnnd.s38353
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mechanisms of neurodegeneration based on the phenotypic expression of progressive forms of immune-mediated neurologic disease

Abstract: Considering there are no treatments for progressive forms of multiple sclerosis (MS), a comprehensive understanding of the role of neurodegeneration in the pathogenesis of MS should lead to novel therapeutic strategies to treat it. Many studies have implicated viral triggers as a cause of MS, yet no single virus has been exclusively shown to cause MS. Given this, human and animal viral models of MS are used to study its pathogenesis. One example is human T-lymphotropic virus type 1-associated myelopathy/tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 155 publications
(301 reference statements)
2
33
0
Order By: Relevance
“…189,190 Pathologically, accumulation of amyloid precursor protein (APP) 15,191 and staining for non-phosphorylated neurofilament (SMI-32) 9 (both markers of axonal injury) showed that axonal damage is a major component of MS lesions. 9,187,192,193 Importantly, several studies have shown the presence of neurodegeneration throughout the disease course of MS, not just during latter progressive phases of disease, as was originally thought. 187 In experimental allergic encephalomyelitis (EAE), an animal model of MS, data indicate that (like in MS) neuronal and axonal damage are present throughout the course of the disease, and thus contribute to the neurologic disability displayed by the animals.…”
Section: Chapter 5 Anti-hnrnp A1 Antibodies Increase Neurodegeneratimentioning
confidence: 89%
See 4 more Smart Citations
“…189,190 Pathologically, accumulation of amyloid precursor protein (APP) 15,191 and staining for non-phosphorylated neurofilament (SMI-32) 9 (both markers of axonal injury) showed that axonal damage is a major component of MS lesions. 9,187,192,193 Importantly, several studies have shown the presence of neurodegeneration throughout the disease course of MS, not just during latter progressive phases of disease, as was originally thought. 187 In experimental allergic encephalomyelitis (EAE), an animal model of MS, data indicate that (like in MS) neuronal and axonal damage are present throughout the course of the disease, and thus contribute to the neurologic disability displayed by the animals.…”
Section: Chapter 5 Anti-hnrnp A1 Antibodies Increase Neurodegeneratimentioning
confidence: 89%
“…spastic paraparesis and ataxia). 11,12,192 In separate in vitro experiments, anti-hnRNP A1 antibodies were found to enter neurons by utilizing endocytosis, a mechanism identical to antibodies isolated from ALS patients and monoclonal antibodies directed at Tau protein. 11,[206][207][208] Further, the anti-hnRNP A1 antibodies caused the mis-localization of hnRNP A1 from predominantly nuclear to an equal nuclear/cytoplasmic distribution suggesting that the anti-hnRNP a1 antibodies bound M9 and disrupted hnRNP A1's normal trafficking between the nucleus and cytoplasm.…”
Section: Chapter 5 Anti-hnrnp A1 Antibodies Increase Neurodegeneratimentioning
confidence: 99%
See 3 more Smart Citations